Analisis Dampak Kehadiran Layanan Go-Food Terhadap Pendapatan dan Laba UMKM di Banjarmasin Timur - Maulidanto, Brillian; Chandriyanti, Ika (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine and describe the impact of Go-food services on the income and profit of culinary MSMEs in East Banjarmasin. The respondents of this study were 36 MSME culinary entrepreneurs with data collection techniques through questionnaires, observation, and documentation. The data analysis technique used was the Mann-Whitney test, a test to see the difference in the median of the two groups. If the data is interval or ratio, then the distribution is abnormal. The results of this study are that Gofood significantly affects the income and profit of culinary MSMEs in the field of snacks and heavy meals.